2021
DOI: 10.1021/acs.biomac.1c00105
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Enzyme-Embedded Plastics

Abstract: A simple and environmentally friendly approach toward the thermoplastic processing of rapidly degradable plastic-enzyme composites using three-dimensional (3D) printing techniques is described. Polycaprolactone/Amano lipase (PCL/AL) composite films (10 mm × 10 mm; height [h] = ∼400 μm) with an AL loading of 0.1, 1.0, and 5.0% were prepared via 3D printing techniques that entail direct mixing in the solid state and thermal layer-by-layer extrusion. It was found that AL can tolerate in situ processing temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…Nevertheless, very promising examples have been published recently for poly‐(L‐lactic acid) (PLA) films and for using embedded proteinase K for self‐degradation (Huang et al, 2020 ). Recently, a very convincing study has demonstrated that using 3D printing with a lipase implemented in PCL as composite films could be a highly attractive technological advancement (Greene et al, 2021 ). Furthermore, the implementation of lipase and/or proteinase K as nano‐dispersed enzymes into PCL and PLA films was shown to be a highly efficient and advanced technology for polymer degradation (DelRe et al, 2021 ).…”
Section: Future Biotechnological Challengesmentioning
confidence: 99%
“…Nevertheless, very promising examples have been published recently for poly‐(L‐lactic acid) (PLA) films and for using embedded proteinase K for self‐degradation (Huang et al, 2020 ). Recently, a very convincing study has demonstrated that using 3D printing with a lipase implemented in PCL as composite films could be a highly attractive technological advancement (Greene et al, 2021 ). Furthermore, the implementation of lipase and/or proteinase K as nano‐dispersed enzymes into PCL and PLA films was shown to be a highly efficient and advanced technology for polymer degradation (DelRe et al, 2021 ).…”
Section: Future Biotechnological Challengesmentioning
confidence: 99%
“…However, depending on the ultimate application goals, entrapping enzymes inside the thermoplastic matrix may be beneficial. Greene et al [ 82 ] mixed solid-state lipase enzyme powder together with dry ground polycaprolactone (PCL) powder and melt-extruded the “thermal paste” in an FDM-like 3D printer. Dry solid enzymes were able to well tolerate the 130 °C processing temperature for 60 min.…”
Section: Immobilization By Physical Entrapment During 3d Printingmentioning
confidence: 99%
“…[ 61 ] An elegant strategy from the research team around Greene utilized heat stable Amano lipase which displayed enzymatic activity even after exposure to 130 °C for 60 min. [ 62 ] Mixing of enzyme and PCL in the solid‐state and thermal layer‐by‐layer extrusion enabled successful 3D printing of enzyme embedded plastics. Importantly, enzyme embedded thin films degraded significantly faster compared to external addition of the same enzyme and enabled 100% weight loss after 7 d in an aqueous buffer at 37 °C.…”
Section: On the Macroscale—incorporation Of Enzymes Into Polymer Mate...mentioning
confidence: 99%
“…Degradation rates of polyesters often depend on the ratio of crystalline to amorphous sections [ 70 ] and crystalline domains are often left untouched by embedded enzymes. [ 62,71 ] For example, a lipase derived from L. plantarum with Tween 20 in chloroform for dispersion into PCL matrices resulted in enzymatic activity predominantly on the amorphous regions of the PCL films. This was confirmed by measuring the crystallinity of the material, showing an increase from 39% to 95% over 8 d as a strong indicator that the crystalline segments are not degraded.…”
Section: On the Microscale—materials Structure And Morphologymentioning
confidence: 99%